Penggunaan Moda Pembelajaran Google Jamboard pada Persamaan Trigonometri untuk Meningkatkan Prestasi Belajar Matematika - Partini Partini (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The achievement in learning trigonometric equations using Google Jamboard instructional moda among 11 th-grade students in MIPA3 class at SMA Negeri 1 Ngaglik during the academic year 2021/2022 can be enhanced. A classroom action research involved 35 students. Data was gathered through daily journals, unstructured interviews, documentation, and assessments conducted in each cycle. Qualitatively descriptive, the study analyzed data through several steps, summarizing information, presenting findings, and drawing conclusions. The research results indicate that the utilization of Google Jamboard in teaching trigonometric equations has improved mathematical learning so that students increasingly understand and develop. This finding is reinforced by data analysis, demonstrating that the teacher's ability in conducting the learning process in cycle I was assessed as good, and the students' test scores by cycle II show that 86% of them have met or exceeded the established learning standards, which are scores equivalent to or greater than 77.